A chemo-mechanical grain boundary model and its application to understand the damage of Li-ion battery materials. (1st July 2020) - Bai, Yang; Zhao, Kejie; Liu, Yao; Stein, Peter; Xu, Bai-Xiang
Graphical abstract: Abstract: Although the unique mechanical and transport features of grain boundaries (GBs) in polycrystalline ion conductors have been recognized, the understanding of the chemo-mechanical interplay and its impact is insufficient. We present a coupled GB model which includes both the damage-dependent across-grain transport and a mechanical cohesive zone law. 3D simulations on  LiNi x Mny Coz O2 demonstrate that the chemical process and the mechanical degradation go hand-in-hand: the enhanced intergranular chemical inhomogeneity challenges the GB mechanical strength, while the GB damage influences or even blocks the across-grain transport. Results explain well the experimentally observed features including chemical hot spots and surface layer delamination.